Phytotoxicity of Essential Oils on Selected Weeds: Potential Hazard on Food Crops - María Dolores Ibáñez; María Amparo Blázquez (Plants, 2018)
The chemical composition of winter savory, peppermint, and anise essential oils, and in vitro and in vivo phytotoxic activity against weeds (Portulaca oleracea, Lolium multiflorum, and Echinochloa crus-galli) and food crops (maize, rice, and tomato), have been studied. Sixty-four compounds accounting for between 97.67–99.66% of the total essential oils were identified by Gas Chromatography-Mass Spectrometry analysis. Winter savory with carvacrol (43.34%) and thymol (23.20%) as the main compounds produced a total inhibitory effect against the seed germination of tested weed. Menthol (48.23%), menthone (23.33%), and iso-menthone (16.33%) from peppermint only showed total seed germination inhibition on L. multiflorum, whereas no significant effects were observed with trans-anethole (99.46%) from anise at all concentrations (0.125–1 µL/mL). Low doses of peppermint essential oil could be used as a sustainable alternative to synthetic agrochemicals to control L. multiflorum. The results corroborate that in vivo assays with a commercial emulsifiable concentrate need higher doses of the essential oils to reproduce previous in vitro trials. The higher in vivo phytotoxicity of winter savory essential oil constitutes an eco-friendly and less pernicious alternative to weed control. It is possible to achieve a greater in vivo phytotoxicity if less active essential oil like peppermint is included with other active excipients.